Callus induction and regeneration from germinating mature embryos of wheat (Triticum aestivum L.) - Tamimi, Samih M.; Othman, Halima (Penerbit Universiti Kebangsaan Malaysia, 2021)
A high-performance protocol for callus induction was devised using germinating mature embryos of two local wheat (Triticum aestivum L.) landraces as explant. The results showed that callus development from germinating embryos was rapid starting one day after culture with an induction rate 20 to 25% higher than those of soaked embryos. In addition, the mean rate of growth of callus developed from germinating embryos was 60 to 70% higher than those cultured from soaked embryos. This study also demonstrated a higher frequency of green spots formation (48 to 56%) on callus derived from germinating embryos compared to their soaked counterpart (24 to 28%), suggesting a better differentiation potential of callus cultures derived from germinating embryo. These findings indicate that germinating mature embryo is more suitable explant for wheat callus induction and regeneration than the soaked mature embryo commonly employed for wheat callus culture.